PERSEPSI GURU TENTANG KOMPETENSI PROFESIONAL GURU DI SEKOLAH MENENGAH KEJURUAN NEGERI SEKECAMATAN PADANG BARAT - Desfitri Ramadhani; Novriyanti Achyar; Hadiyanto; Tia Ayu Ningrum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe teachers' perceptions regarding professional competence among teachers at state vocational high schools (SMK Negeri) in the Padang Barat District. This is a quantitative descriptive study. The population consisted of 145 teachers, with a sample of 108 teachers selected using the Proportional Random Sampling technique. The research instrument was a Likert-scale questionnaire that had undergone validity and reliability testing. Data were analyzed using descriptive statistics by calculating the mean score. The results indicate that teachers' perceptions of professional competence at state vocational high schools in the Padang Barat District fall into the